The Effect of Profitability, Leverage, and Capital Intensity on Tax Planning Moderated by Firm Size in Real Estate Companies (2022–2024) - Febyansyah, Andar; Wijaya, Micko Surya (SAFE-Network, 2026)
This study identifies the impact of profitability, leverage, and capital intensity on tax planning, with company size as a moderating variable, focusing on real estate companies listed on the Indonesia Stock Exchange (IDX) for the years 2022 to 2024. This study uses a quantitative method with moderated regression analysis (MRA). The sample consists of 37 companies that meet certain criteria, resulting in 111 panel data observations. The findings show that profitability has a significant positive effect on tax planning, while leverage has a significant negative effect on tax planning, and capital intensity has a significant positive effect on tax planning. Company size does not moderate the relationship between profitability, leverage, and capital intensity on tax planning. The managerial implication of this study is the importance of company management to pay attention to the balance between tax efficiency and tax compliance so as not to trigger legal risks and damage to reputation.